2022
DOI: 10.1111/nph.18008
|View full text |Cite
|
Sign up to set email alerts
|

A rice single cell transcriptomic atlas defines the developmental trajectories of rice floret and inflorescence meristems

Abstract: Rice inflorescence development determines yield and relies on the activity of axillary meristems (AMs); however, high-resolution analysis of its early development is lacking.Here, we have used high-throughput single-cell RNA sequencing to profile 37 571 rice inflorescence cells and constructed a genome-scale gene expression resource covering the inflorescence-to-floret transition during early reproductive development. The differentiation trajectories of florets and AMs were reconstructed, and discrete cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 98 publications
(170 reference statements)
0
35
0
Order By: Relevance
“…By high-throughput single-cell RNA sequencing technology, auxin influx transporter gene OsAUX1 is identified to have enriched expression in BM. Consistent with its expression pattern, the loss-of-function mutant of OsAUX1 produces smaller inflorescence with reduced branch and spikelet number ( Zong et al., 2022 ).…”
Section: Roles Of Phytohormones In Controlling Inflorescence Architec...mentioning
confidence: 77%
“…By high-throughput single-cell RNA sequencing technology, auxin influx transporter gene OsAUX1 is identified to have enriched expression in BM. Consistent with its expression pattern, the loss-of-function mutant of OsAUX1 produces smaller inflorescence with reduced branch and spikelet number ( Zong et al., 2022 ).…”
Section: Roles Of Phytohormones In Controlling Inflorescence Architec...mentioning
confidence: 77%
“…In addition to the applications in Arabidopsis primary root tips, scRNA‐seq has been applied to study other dicots and monocots, as well as in leaves, inflorescences, and other tissues (Sun et al., 2022a; Zong et al., 2022). More recently, it was found that CYCLING DOF FACTOR 5 (CDF5) and REPRESSOR OF GA (RGA) have potential roles in the early development and function of leaf veins in cotyledons (Liu et al., 2022b).…”
Section: Single‐cell Transcriptomicsmentioning
confidence: 99%
“…New technologies can help define homologies: single‐cell RNA sequencing, which analyzes gene expression in thousands of cells across spatial and temporal gradients, has revealed genetic underpinnings of developmental trajectories in rice spikelets. Despite morphological similarity of lemmas and paleas in rice, lemma gene expression is similar to that of glumes, while palea gene expression is similar to that of lodicules and reproductive organs (Zong et al, 2022). This expression pattern again suggests that lemmas, with gene expression patterns more similar to bracts, may be homologous to bracts.…”
Section: Mutants and Genomics Suggest More Complexitymentioning
confidence: 99%